1568. Implementation of a Standard Diet Regimen for Neutropenic High-Risk Cancer Patients: Effects on Incidence of Infections, Foodborne Diseases, and Outcome. (26th November 2018) - Jakob, Carolin; Löhnert, Annika Y; Stecher, Melanie; Engert, Andreas; Freund, Meike; Hamprecht, Axel; Jazmati, Nathalie; Wisplinghoff, Hilmar; Hallek, Michael; Cornely, Oliver A; Vehreschild, Janne
Abstract: Background: Neutropenia is a major risk factor for infections in cancer patients. Even though evidence to support a germ-free neutropenic diet (ND) is missing, many oncology departments still maintain ND regimens. While benefits of an ND remain uncertain, restrictions of food and rigorous preparation rules impact quality of life and may further increase malnutrition rates in cancer patients. Methods: Based on the Cologne Cohort of Neutropenic Patients database, we conducted a retrospective analysis of high-risk hematological/oncological patients with a confirmed period of neutropenia (neutrophils < 500/mm 3 ) which lasted longer than 5 days. The interval of four years before and after replacing the ND by a standard hospital diet (SD) in January 2008 was compared. Patients undergoing allogenic stem-cell transplantation were excluded. The relative days of febrile neutropenia (relFN) before (neutropenic diet group, NDG) and after (standard diet group, SDG) the change of diet were analyzed in a propensity score-matched cohort. Secondary outcomes were the incidence of food borne disease, bloodstream infections (BSI), antibiotic treatment, diarrhea, weight change, nausea, and death. Results: A total of 774 neutropenic episodes of each NDG and SDG were included into the analysis. The median days of neutropenia were 11 (IQR 8–16) in the NDG and 10 (IQR 8–16) in the SDG ( P = 0.320). The rate of acute leukemia for NDG and SDG was 47% ( P = 0.839). The mean relFN was 0.20 in the NDG and 0.22 in the SDG ( P = 0.270). In our multivariate model, no association between diet and relFN was identified (OR 0.03; IQR −0.04–0.09; P = 0.410). Diarrhea occurred in 52% in the NDG and 40% in the SDG ( P < 0.001), nausea in 72% and 66% ( P < 0.001). No significant changes in frequency of gastrointestinal infections (NDG: 2; SDG: 1; P = 0.719) or BSI related to foodborne disease (NDG: 0; SDG: 3 P = 0.248) were detected after change of diet. The detected BSI (NDG: 29%; SDG: 30%; P = 0.867), antibiotic treatment (NDG: 78%; SDG: 77%; P = 0.760), weight gain (NDG: 11%; SDG: 14%; P = 0.121), and median 28-day mortality (NDG: 13.5 (IQR 8.8–32.5); SDG: 17 (IQR 10–29); P = 0.118) were equally distributed after change of diet (see Figure 1). Conclusion: We did not detect a change in relFN after replacing the ND with an SD. In our population, an SD was safe for neutropenic high-risk patients. Disclosures: All authors: No reported disclosures.